Classification of decomposable Manin triples and solutions of the classical Yang-Baxter equation - Pantev, Tony; Tsanov, Vasil (Ann. Sofia Univ. Fac. Math. and Inf., 1995)
We classify decomposable triple Manin over an arbitrary smooth algebraic curve and describe the corresponding solutions of the classical Yang-Baxter equation. We also give some examples and countar-examples clarifying the nature of the correspondence between general triple Manin systems and solutions of the classical yang-Baxter equation.